Topic extraction from adverbial clauses - Rubio Alcalá, Carlos (Borealis – An International Journal of Hispanic Linguistics, 2016)
This paper offers new data to support findings about Topic extraction from adverbial clauses. Since such clauses are strong islands, they should not allow extraction of any kind, but we show here that if the appropriate conditions are met, Topics of the CLLD kind in Romance can move out of them. We propose that two conditions must be met for such movement to be possible: the first is that the adverbial clause must have undergone topicalisation in the first place; the second is that the adverbial clause is inherently topical from a semantic viewpoint. Contrast with other language families (Germanic, Quechua and Japanese) is provided and the semantic implications of the proposal are briefly discussed. Keywords: topicalisation; Clitic Left Dislocation; syntactic islands; adverbial clauses Este artículo ofrece nuevos datos sobre la extracción de Tópicos desde oraciones subordinadas adverbiales. Dado que dichas oraciones son islas fuertes, no deberían permitir extracción de ningún tipo, pero mostramos que si se dan las condiciones apropiadas, los Tópicos del tipo CLLD en lenguas románicas pueden desplazarse fuera de ellas. Proponemos que se deben cumplir dos condiciones para que ese movimiento sea posible: la primera es que la propia subordinada adverbial se haya topicalizado en primer lugar; la segunda es que la subordinada adverbial sea inherentemente un Tópico desde el punto de vista semántico. Proporcionamos también algunos contrastes con otras familias lingüísticas (germánica, quechua y japonés) y se discuten brevemente las implicaciones semánticas de la propuesta. Palabras clave: topicalización; dislocación a la izquierda con clítico; islas sintácticas; oraciones adverbiales